2022
DOI: 10.1002/edn3.297
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging eDNA metabarcoding to characterize nearshore fish communities in Southeast Alaska: Do habitat and tide matter?

Abstract: Nearshore marine habitats are critical for a variety of commercially important fish species, but assessing fish communities in these habitats is costly and time‐intensive. Here, we leverage eDNA metabarcoding to characterize nearshore fish communities near Juneau, Alaska, USA, a high‐latitude environment with large tidal swings, strong currents, and significant freshwater input. We investigated whether species richness and community composition differed across three habitat types (sand beaches, eelgrass beds, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 68 publications
4
9
1
Order By: Relevance
“…In our study, the tidal flow had no significant effect on the species assemblage recovered from the eDNA approach, although water movement is driven by the tide at Helgoland Roads. The same was found in other studies examining the tidal influence on species detection (Bleijswijk et al, 2020; Kelly et al, 2018; Lafferty et al, 2021; Larson et al, 2022). However, one study identified a significant effect of tides but this explained only 8% of the observed variation (Ely et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the tidal flow had no significant effect on the species assemblage recovered from the eDNA approach, although water movement is driven by the tide at Helgoland Roads. The same was found in other studies examining the tidal influence on species detection (Bleijswijk et al, 2020; Kelly et al, 2018; Lafferty et al, 2021; Larson et al, 2022). However, one study identified a significant effect of tides but this explained only 8% of the observed variation (Ely et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Data were processed using methods similar to Larson et al (2022). Raw sequencing reads were trimmed of primers using Cutadapt (Martin, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Other ASVs that were assigned to fish or mussel species not present in Michigan based on distributional information from the FishBase (https://www.fishb ase.org) and Nature Explorer databases (https://explo rer.natur eserve.org) were removed. Full taxonomy of the remaining ASVs was determined from NCBI taxonomy using custom scripts (Larson et al, 2022). Any ASVs that matched a single species at ≥98% similarity was assigned to that species.…”
Section: Data Processingmentioning
confidence: 99%
“…Environmental impact on shedding and degradation of DNA must be further investigated for a more accurate interpretation of eDNA concentrations for biomass estimation. While DNA shedding and degradation rates alone could be used to estimate fish biomass, an optimal approach would include an oceanographic model framework that accounts for DNA dispersal and exposure to conditions affecting degradation (Larson et al, 2021).…”
Section: Applying Biomass Estimation To Field Studiesmentioning
confidence: 99%